2022
DOI: 10.1002/srin.202200304
|View full text |Cite
|
Sign up to set email alerts
|

Study on Properties of Cold‐Bonded Briquettes Prepared from Return Fines of Sinter

Abstract: Return fines of sinter (return fines) are used to prepare cold‐bonded briquettes (CBBs). The reduction disintegration index (RDI) of RDI+3.15 and compressive strength after RDI experiment of CBB are higher than that of the sinter. For microscopic morphologies after RDI experiment, cracks initiate in the area of the return fines but do not propagate through the whole matrix of CBB. The reduction index (RI) of CBB is lower than that of the sinter; conversely, the compressive strength of CBB after RI experiment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…CBBC comprised 84 wt% of return fines, 7 wt% of compound binder, and 9 wt% of nut coke. According to our previous studies, the amount of binder and coke nut added was set at 7% and 9%, respectively, to ensure that the cold‐bonded briquette's strength and reducibility satisfy the demands of a blast furnace [ 1 ] . The nut coke was ground to a fineness of less than 0.5 mm to ensure it is entirely utilized.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…CBBC comprised 84 wt% of return fines, 7 wt% of compound binder, and 9 wt% of nut coke. According to our previous studies, the amount of binder and coke nut added was set at 7% and 9%, respectively, to ensure that the cold‐bonded briquette's strength and reducibility satisfy the demands of a blast furnace [ 1 ] . The nut coke was ground to a fineness of less than 0.5 mm to ensure it is entirely utilized.…”
Section: Methodsmentioning
confidence: 99%
“…Return fines of sinter is now being utilized in blast furnaces straight after cold briquetting, a novel method of return fines utilization. [ 1–4 ] This technique can prevent return fines from being repeatedly sintered at high temperatures. On the one hand, it can lower the amount of energy used by the sinter plant, and on the other, it can increase the output of the sintering process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some studies have explored the possibility of dust briquette recycling in converters and rotary hearth furnaces. [12,18] Through a review of previous literature, it is found that the current research on dust briquette mainly focuses on all-dust briquette, that is, both carbon reducing agents and iron oxides generated during the production of iron and steel. Furthermore, research has predominantly centered on investigating the reduction behavior of individual briquette in blast furnaces, briquette there is limited research on the impact of dust briquette on the softening-melting zone of blast furnaces.…”
Section: Introductionmentioning
confidence: 99%